Competitive Strategies In Quantity Surveying (Qs) Firms During The Economic Turbulence Period (2006-2010) In Malaysia - Adros, Nur Azila (2013)
Rapid change in the global marketplace offers formidable challenges to firms in the construction industry. These firms need to apply competitive strategies appropriate to their objectives to keep an edge over the competition. By offering professional service in the industry, quantity surveying (QS) firms are different from product-based industries in terms of services provided, relationship between firm-client, and competitive style with existing and new firms. Four common types of competitive strategies exist in the industry: cost-leadership, focus, differentiation, and growth strategies. Selecting the most appropriate competitive strategy to remain resilient in the industry is essential for QS firms. The success of any strategy adopted is determined by the performance of the firm. This research aims to investigate the application of competitive strategies of QS firms by studying the strategies applied by these firms during the economic turbulence period (2006 to 2010). First, this research identifies the strategy adopted within five years, that is, from 2006 to 2010. Second, it identifies the competitive strategies applied by QS firms based on their sizes. Finally, it examines the business performance of QS firms. A survey has been conducted among QS firms located in Kuala Lumpur and Selangor, and the response rate is 48%. The data gathered is analysed using descriptive analysis. The finding for the first objective reveals that differentiation strategy is the most preferred competitive strategy, whereas growth strategy is the least preferred. For the second objective, the finding indicates that differentiation strategy is the most applied competitive strategy among small, medium-sized, and large firms. Under differentiation strategy, ‘branding strategies’ is the most important competitive element for all firm sizes.